Music interaction with others as conveyor of relational intent: A response to Cross (2014). (November 2014) - Chew, Elaine
In 'Music and communication in music psychology, ' Ian Cross presents the idea that music may be 'an optimal means of managing situations of social uncertainty' through its properties of entrainment and floating intentionality. Complementary to speech, music offers primarily a relational (as opposed to transactional) dimension to communication. While music cannot communicate abstract information or meaning, I posit that its requirement for entrainment can convey relational intent directly and unambiguously, to which one could then attribute the sense of honest communication and alignment described by Cross. Musical engagement with others exposes behavioural tendencies through the participants' willingness for, and nature of, cooperation. Thus, while active engagement with others through music cannot reveal what one thinks (hence the floating intentionality), it can demonstrate how one thinks (relational intent). According to Cross, music acts as 'an honest signal revealing attitudes and motivations' in unscripted, participatory music making. I venture further to say that this relational honesty extends to scripted (and partially-scripted) music in a real and tangible way. The joint shaping of expressive forms that rise to the fore in scripted music offer experiences of reciprocity, and of honest communication of intent, akin to spontaneous dialogue in speech and unscripted music.